PHYSIOLOGICAL SOLUTION (NaCl 0,9%) AS ONE OF THERAPIES IN PATIENTS WITH ORAL LESIONS ASSOCIATED WITH STEVEN-JOHNSON SYNDROME - I Nyoman Gede Juwita Putra; Riani Setiadhi (FKG ULM, 2025)
Background. Steven-Johnson Syndrome (SJS) is a hypersensitivity reaction characterized by acute blisters and necrosis of the skin and mucous membranes, triggered by drugs. This case occurs in 1 or 2: 1000,000 cases. Objectives. This case report aims to describe the role of NaCl 0,9% solution as one of the therapies in patients with oral lesions associated with SJS. A 40-year-old woman was consulted by the Internal Medicine Department with complaints of pain on lips approximately 3 days before, difficulty opening mouth and bleeding lips easily. Patients consumed Carbamazepin, Amitriptiline, Paracetamol, and Cefixime. Extraoral examination showed lips with erosive lesions accompanied by blackish sanguinolenta crusting, pain, tend to bleed. Intraoral examination showed white plaque on the dorsum of the tongue. The patient was diagnosed with oral lesions associated with SJS et causa Carbamazepin, and/or Amitriptiline and/or Cefixime, and/or Paracetamol. Treatment. Based on the diagnosis, the pharmacological management is intravenous dexamethasone 5mg by the Dermatology and Venereology division, while Oral Medicine treatment is compressing the lips with a NaCl 0,9% solution three times a day. After the 4th day of therapy, oral lesions were repaired. NaCl 0,9% solution as moist wound healing has the principle of moisturizing by keeping the condition of the wound base moist to facilitate cell migration at the base of the wound. The moist environment allows neutrophils and macrophages to migrate better so as to provide the best environment for the healing process. Conclusion. NaCl 0,9% has an important role in the oral lesions healing process in SJS. Keywords: haling lesions, NaCl 0,9%, steven-johnson syndrome.